Burden of kidney cancer and attributed risk factors in China from 1990 to 2019 - Wang, Zongping; Wang, Le; Wang, Song; Xie, Liping (Frontiers in Public Health, 2022)
Background: Kidney cancer is a common type of cancer; however, the changing trends and risk-attributed burdens in China are unknown. Therefore, this study aimed to describe the latest status and trends of kidney cancer burden in China and its associated risk factors. Methods: The absolute numbers and rates of the incidence, death, and disability-adjusted life years (DALYs) of kidney cancer in China were extracted from the Global Burden of Disease 2019 platform. Overall burden and burden attributed to smoking and high body mass index (BMI) were described. Average annual percent change (AAPC) was calculated to describe trend analyses from 1990 to 2019 using the Joinpoint regression program. Results: In 2019, 59,827 new cases, 23,954 deaths, and 642,799 DALYs of kidney cancer occurred in China, of which males accounted for 71.1%, 70.5%, and 72.0%, and the population aged  55 years accounted for 58.9%, 77.9%, and 60.1%, respectively. From 1990 to 2019, the age-standardized incidence rate (per 100,000 person-years) increased from 1.16 in 1990 to 3.21 in 2019, with an AAPC of 3.4% (95% confidence interval [CI] :3.1% to 3.8%, P < 0.05); the mortality rate increased from 0.70 to 1.27, with an AAPC of 2.1% (1.5% to 2.3%, P < 0.05); and the DALY rate increased from 0.70 to 1.27, with an AAPC of 2.1% (1.5% to 2.3%, P < 0.05). In 2019, the proportions of DALYs attributed to smoking, and high BMI were 18.0% and 11.1%, respectively, and the DALY rates attributed to both smoking and high BMI increased from 1990 to 2019, with AAPC of 2.9% (2.6% to 3.3%, P < 0.05) and 4.8% (4.2% to 5.4%, P < 0.05), respectively. Conclusion: The kidney cancer burden in China has continued to grow over the past 3 decades, with a severe burden among older adults and males. Therefore, timely preventive interventions for modifiable risk factors are required.